2016
DOI: 10.1523/jneurosci.1353-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Habenula-Induced Inhibition of Midbrain Dopamine Neurons Is Diminished by Lesions of the Rostromedial Tegmental Nucleus

Abstract: Phasic changes in the activity of midbrain dopamine cells motivate and guide future behavior. Activation of the lateral habenula by aversive events inhibits dopamine neurons transiently, providing a neurobiological representation of learning models that incorporate negative reward prediction errors. Anatomical evidence suggests that this inhibition occurs via the rostromedial tegmental nucleus, but this hypothesis has yet to be tested directly. Here, we show that axon-sparing lesions of the rostromedial tegmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 56 publications
1
40
0
Order By: Relevance
“…It has been shown that stimulation of the RMTg inhibits both the VTA and the SNc (Hong et al 2011;Bourdy et al 2014;Lecca et al 2012), and RMTg inhibition increased DA neurons activity (Jalabert et al 2011). Recently, Brown and collaborators have shown that RMTg neurons contribute directly to the LHb-induced inhibition of DA neurons activity (Brown et al 2017). The RMTg receives afferents from a wide range of cerebral structures (for review see (Bourdy and Barrot 2012)) such as the cortex, the periaqueducal gray, the LDTg and PPTg, suggesting that the RMTg may integrate a variety of information that can modulate activity of both the VTA and SNc.…”
Section: Addiction and The Addiction Cyclementioning
confidence: 99%
“…It has been shown that stimulation of the RMTg inhibits both the VTA and the SNc (Hong et al 2011;Bourdy et al 2014;Lecca et al 2012), and RMTg inhibition increased DA neurons activity (Jalabert et al 2011). Recently, Brown and collaborators have shown that RMTg neurons contribute directly to the LHb-induced inhibition of DA neurons activity (Brown et al 2017). The RMTg receives afferents from a wide range of cerebral structures (for review see (Bourdy and Barrot 2012)) such as the cortex, the periaqueducal gray, the LDTg and PPTg, suggesting that the RMTg may integrate a variety of information that can modulate activity of both the VTA and SNc.…”
Section: Addiction and The Addiction Cyclementioning
confidence: 99%
“…Called the ‘tail of the VTA’ by one group (Perrotti et al, 2005, Kaufling et al, 2009), these neurons are now better known as the rostromedial tegmental nucleus (RMTg; Jhou et al, 2009a; b). The timely discovery of the RMTg provides an explanation as to how activation of LHb neurons by aversive stimuli (Christoph et al, 1986; Ullsperger and von Cramon, 2003; Brown et al, 2017) elicits profound inhibition of VTA DA neurons (Ji and Shephard, 2007; Shepard et al, 2006; Matsumoto and Hikosaka, 2007). The opposing valences of LHb and VTA/SNc responses to reward omission and aversive stimuli previously had been difficult to reconcile because the axonal projection from the LHb to the VTA is almost exclusively excitatory (Geisler et al, 2007; Brinschwitz et al, 2010), which dictated a need for an inhibitory intermediary – the RMTg, it turned out - to account for the functional findings (see the discussion in Ji and Shephard, 2007).…”
Section: Efferent Connectionsmentioning
confidence: 99%
“…Golden et al used a place preference conditioning paradigm to demonstrate the rewarding value of winning: after aggressive mice attacked and subordinated an intruder, they developed a preference for the intruder-paired chamber. When the LHb was artificially activated by optogenetically silencing an inhibitory input to the LHb, the rewarding effect of winning was blocked [67]. Thus, reducing activity of the LHb which presumably increasing activity of VTA dopamine neurons is essential for the rewarding effect of winning.…”
Section: Mesolimbic Dopamine Control Of Aggressive Behaviorsmentioning
confidence: 99%